Expression of two histone H4 epigenetic modifications (lysine 12 acetylation and lysine 20 trimethylation), and the senescence marker lamin B1 in the postnatal, adult, and old mouse brain - Sbriz, Marco; Shamshiddinova, Maftuna; Lossi, Laura; Merighi, Adalberto (Frontiers in Cell Death, 2025)
Aging is a complex biological process characterized by gradual cellular and molecular changes contributing to cognitive decline and neurodegeneration. Histone alterations regulate gene expression, chromatin organization, and neuronal function. Additionally, nuclear architecture undergoes significant alterations during aging, with lamin B, a key component of the nuclear lamina, playing a pivotal role in maintaining the stability of the cell nucleus. Lamin B1 (LB1) dysfunction has been implicated in age-related neuronal decline, as aberrations in its expression or processing can lead to nuclear deformation, impaired gene regulation, and increased susceptibility to DNA damage to the point that LB1 is now regarded as a cellular senescence marker. We have studied the immunocytochemical localization of trimethylated histone H4 at lysine 20 (H4K20me3), acetylated histone H4 at lysine 12 (H4K12ac), and LB1 in the brain of postnatal day 5 (P5) pups, mature adult (9–10 months), and old (24 months) mice, aiming to find a correlation between histone epigenetic modifications, senescence, and cell death, with particular attention to the hippocampus and cerebral cortex. We first describe the distribution of the three molecules throughout the different brain regions, and confirm these data with Western blot analysis. We then show that H4K20me3 and H4K12ac can be detected in both neurons and glia. After inferential statistics and effect size analysis, we demonstrate that a biologically meaningful reduction in the expression of the three molecules occurs in the old hippocampus. In addition, a biologically relevant decrease in the degree of cellular coexistence of H4K20me3 and H4K12ac was observed in the hippocampus and cerebral cortex. Understanding how histone and LB1 modifications influence brain aging provides valuable insights into the molecular pathways that drive neurodegeneration and may offer clues to better understanding age-related cognitive disorders.